The Impact of Health Education Using Audio-Visual Media on the Family's Role in LBW Care at Mutia Sari Hospital, Duri, Riau - Helfrida Situmorang; Sri Dewi Br Siregar; Nopita Yanti Sitorus (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Low birth weight (LBW) is a major neonatal health concern that places considerable demands on families, who often lack adequate knowledge and skills to care for their infants. Health education through audiovisual media offers a concrete and engaging means of strengthening the family's caregiving role. This study aimed to determine the effect of health education using audiovisual media on the family's role in caring for LBW infants at Mutia Sari Hospital, Duri, Riau. A quantitative quasi-experimental design with a one-group pretest–posttest approach was employed. The population comprised all families of LBW patients at the hospital, and 30 respondents were selected through total sampling. Data on the family's role were collected using a validated questionnaire and analyzed using the Wilcoxon signed-rank test. Before the intervention, the family's role was predominantly in the poor category (50.0%), whereas after the intervention, the majority shifted to the adequate category (46.7%), with the good category rising to 36.7% and the poor category declining to 16.7%. The Wilcoxon signed-rank test yielded Z = −3.272 with a p-value of 0.001 (p < 0.05), indicating a statistically significant difference in the family's role before and after the intervention. It is therefore concluded that health education using audiovisual media significantly improved the family's role in LBW care, and it is recommended that nurses integrate this approach into routine maternal and neonatal care Keywords: Health education, Audiovisual media, Family role, Low birth weight, Neonatal care